Molecular clustering of patients with Mycobacterium tuberculosis strains cultured from the diabetic and non-diabetic newly diagnosed TB positive cases. (August 2018) - Mburu, Josephine W.; Kingwara, Leonard; Esther, Magiri; Andrew, Nyerere
Abstract: Background: Social determinants of health, biological, and individual variants have been associated with Pulmonary TB (PTB) case clustering. None of the studies have focused on diabetes mellitus (DM) despite it being one of the co-morbidity affecting TB patients. Minimal data is available and it is not clear whether patients with DM and TB are more likely than TB patients without DM to be grouped into similar molecular clusters thus indicating a bias in transmission among TB/DM co-morbidity patients. Objective: To determine proportion of TB strains within TB and TB/DM cases that were clustered with their corresponding clinical outcomes and hence could be attributable to active TB transmission in the two urban counties of Nairobi, Kenya. Methods: We carried out a prospective cohort study of non-pregnant patients aged 15 years and above that tested positive for TB in two peri‑urban counties in Kenya between February 2014 and August 2015. Clinical and socio-demographic data were obtained from a questionnaire and medical records of the National TB program patient data base at two, three, five and six months. Spoligotyping data was then obtained and compared from previously identified strains in a data bank from the spolDB4. Results: We identified 7 different TB strains out of which East Asia Beijing, Euro America and Indo oceanic being the most dominant strain within the two counties accounting for 92.4% of the infections. DM was not a significant factor in increasing the likelihood of PTB patients to cluster according to the genotype of the infecting Mycobacterium tuberculosis bacillus. TB lineages, DM and County of the patient were found to be independent of the clinical outcomes that were observed in the study Conclusion: Diabetes mellitus is not a significant factor in increasing the molecular clustering among PTB patients.